2022
DOI: 10.1371/journal.pone.0278825
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and predictors of Long COVID among diagnosed cases of COVID-19

Abstract: Background Long COVID or long-term symptoms after COVID-19 has the ability to affect health and quality of life. Knowledge about the burden and predictors could aid in their prevention and management. Most of the studies are from high-income countries and focus on severe acute COVID-19 cases. We did this study to estimate the incidence and identify the characteristics and predictors of Long COVID among our patients. Methodology We recruited adult (≥18 years) patients who were diagnosed as Reverse Transcripti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 28 publications
(39 reference statements)
0
18
1
Order By: Relevance
“…Secondly, one third of the positive effect is due to a lower prevalence, in Italy, of underlying conditions likely associated with a higher risk of developing PCC, as widely supported in literature [30][31][32][33]. Interestingly, nonmodifiable risk factors are unlikely to determine differences between the two nations, as both older age and female-male ratio are similar in both countries [34].…”
Section: Discussionmentioning
confidence: 86%
“…Secondly, one third of the positive effect is due to a lower prevalence, in Italy, of underlying conditions likely associated with a higher risk of developing PCC, as widely supported in literature [30][31][32][33]. Interestingly, nonmodifiable risk factors are unlikely to determine differences between the two nations, as both older age and female-male ratio are similar in both countries [34].…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, in Eastern India, researchers found that 29.2% self-reported having long COVID symptoms 4 weeks after diagnosis [53], however they also found that the prevalence on long COVID after infection with only Omicron variant was 8.2% [54]. Lastly, prior studies have also supported that vaccination could reduce the risk of the post-acute sequelae of COVID-19 [55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a longitudinal observation of 371 patients from India confirmed that predictors of long COVID, with fatigue being its most common self-reported symptom, included pre-existing medical conditions, vaccination status, a higher number of acute COVID-19 symptoms, and the severity of infection, but not sex [14]. In a cross-sectional study of two urban centres in Spain among 360 hospitalised patients assessed via telephone interviews two years after the acute phase of the SARS-CoV-2 infection, it was found that a number of comorbidities and dyspnoea were associated with post-COVID fatigue, but not sex [15].…”
Section: Introductionmentioning
confidence: 99%